1995
DOI: 10.1103/physrevb.52.8
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal strains and onset of plasticity in shocked LiF crystals

Abstract: We report experimental determinations of the elastic component of the transverse strain during passage of a shockwave. A 1 ns laser pulse drove an =60 kbar shock into an aluminum coated, radiation hardened, pure LiF single crystal. By diffracting a 0.25 ns pulse of x rays from a nearby high brightness, time-synchronized laser plasma, we measured the simultaneous compression of the lattice both parallel and transverse to the shock propagation direction with subnanosecond resolution. Definite compression was rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
17
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…1 Since the pioneering efforts of Johnson et al [2][3][4] in the early 1970s, different attempts have been reported in the literature [5][6][7][8][9][10][11][12] including the recent work by Wark and co-workers using laser-induced shocks. [10][11][12] A careful examination of the reported attempts revealed that various limitations in the existing studies ͑less than optimal x-ray quality, spatial and temporal nonuniformites of shock loading, use of free surface measurements, etc.͒ have precluded quantitative measurements and analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Since the pioneering efforts of Johnson et al [2][3][4] in the early 1970s, different attempts have been reported in the literature [5][6][7][8][9][10][11][12] including the recent work by Wark and co-workers using laser-induced shocks. [10][11][12] A careful examination of the reported attempts revealed that various limitations in the existing studies ͑less than optimal x-ray quality, spatial and temporal nonuniformites of shock loading, use of free surface measurements, etc.͒ have precluded quantitative measurements and analysis.…”
mentioning
confidence: 99%
“…In contrast, large shock compression along the ͓100͔ direction reportedly results in an isotropic compression of the unit cell. 3,8,12 The experimental configuration for obtaining x-ray diffraction data from shocked single crystals is shown schematically in Fig. 1.…”
mentioning
confidence: 99%
“…Indeed, such time-resolved X-ray diffraction (TXRD) methods have been used extensively to study shock phenomena for several decades [12][13][14][15][16][17][18][19][20] , with several notable successes, including the direct observation of the a À e transition in shock-compressed iron 6,21 . Some progress in understanding rapid shock-induced plasticity has been made: diffraction of monochromatic X-rays from planes parallel and perpendicular to the shock propagation direction has directly detected elastic strain in both directions (which gives a measure of plastic strain, as the total strain (elastic plus plastic) perpendicular to the shock propagation direction in a uniaxially strained material is zero) 16,[22][23][24][25] . Furthermore, broadening of the diffraction peaks observed in both shocked copper 25 , aluminium 26 and LiF 27 are consistent with large defect densities and/or lattice rotations.…”
mentioning
confidence: 99%
“…2 Provided one succeeds in generating short bursts of electrons or X-rays, both electron diffraction and X-ray diffraction [38][39][40][41][42][43][44][45][46][47][48][49] can be adapted to the time domain. Indeed, developments of the recent past have shown that it is possible to generate pulses of even subpicosecond duration of both X-rays 49-51 and electrons.…”
mentioning
confidence: 99%